Mechanisms Underlying the Antidepressant Response of Acupuncture via PKA/CREB Signaling Pathway - Huili Jiang; Xuhui Zhang; Yu Wang; Huimin Zhang; Jing Li; Xinjing Yang; Bingcong Zhao; Chuntao Zhang; Miao Yu; Mingmin Xu; Qiuyun Yu; Xingchen Liang; et al. (Neural Plasticity)
Protein kinase A (PKA)/cAMP response element-binding (CREB) protein signaling pathway, contributing to impaired neurogenesis parallel to depressive-like behaviors, has been identified as the crucial factor involved in the antidepressant response of acupuncture. However, the molecular mechanisms associated with antidepressant response of acupuncture, neurogenesis, and depressive-like behaviors ameliorating remain unexplored. The objective was to identify the mechanisms underlying the antidepressant response of acupuncture through PKA signaling pathway in depression rats by employing the PKA signaling pathway inhibitor H89 in in vivo experiments. Our results indicated that the expression of hippocampal PKA-α and p-CREB was significantly downregulated by chronic unpredicted mild stress (CUMS) procedures. Importantly, acupuncture reversed the downregulation of PKA-α and p-CREB. The expression of PKA-α was upregulated by fluoxetine, but not p-CREB. No significant difference was found between Acu and FLX groups on the expression of PKA-α and p-CREB. Interestingly, H89 inhibited the effects of acupuncture or fluoxetine on upregulating the expression of p-CREB, but not PKA-α. There was no significant difference in expression of CREB among the groups. Conclusively, our findings further support the hypothesis that acupuncture could ameliorate depressive-like behaviors by regulating PKA/CREB signaling pathway, which might be mainly mediated by regulating the phosphorylation level of CREB.